Evolution of irradiation defects in Ti2AlC ceramics during heavy ion irradiation. Issue 12 (15th August 2018) - Wang, Fei; Su, Qing; Nastasi, Michael; Kirk, Marquis A.; Li, Meimei; Cui, Bai
Abstract: The evolution of irradiation defects in Ti2 AlC under Kr ion irradiation at room and elevated temperatures has been investigated. The dependence of defect size and density on the irradiation dose and temperature was characterized by in-situ transmission electron microscopy (TEM) irradiation experiments. At 25–800 °C, interstitial-type dislocation loops with several nanometers in diameter form on the basal plane of Ti2 AlC mostly with a Burgers vector of 1/2[0 0 0 1], and no voids have been observed. The number density of dislocation loops approaches saturation at a level of about 2 dpa at 800 °C. Ti2 AlC samples remain crystalline in structure without amorphization or phase transformation. However, the localized disorder of atomic positions on the basal plane of the irradiated Ti2 AlC was revealed by high-resolution transmission electron microscopy (HRTEM) studies, which increases with irradiation dose while decreases with elevated temperatures.